If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -2(x + 4) = 4x + -7 Reorder the terms: 10x + -2(4 + x) = 4x + -7 10x + (4 * -2 + x * -2) = 4x + -7 10x + (-8 + -2x) = 4x + -7 Reorder the terms: -8 + 10x + -2x = 4x + -7 Combine like terms: 10x + -2x = 8x -8 + 8x = 4x + -7 Reorder the terms: -8 + 8x = -7 + 4x Solving -8 + 8x = -7 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -8 + 8x + -4x = -7 + 4x + -4x Combine like terms: 8x + -4x = 4x -8 + 4x = -7 + 4x + -4x Combine like terms: 4x + -4x = 0 -8 + 4x = -7 + 0 -8 + 4x = -7 Add '8' to each side of the equation. -8 + 8 + 4x = -7 + 8 Combine like terms: -8 + 8 = 0 0 + 4x = -7 + 8 4x = -7 + 8 Combine like terms: -7 + 8 = 1 4x = 1 Divide each side by '4'. x = 0.25 Simplifying x = 0.25
| 40+50m=365 | | x+x+89=180 | | 5+11p=71 | | 128=2(6y-2) | | -4x+5x=-16 | | 15+x=3*x-15 | | 12+2x=24-2x | | (45-x)/x=23 | | 47=3+11h | | b(x^2)-ab=0 | | 7x-30=205 | | 7=w-(-7)5 | | x-10=6x+4 | | 6*x+4=x-11 | | x-26=10 | | 2x-2=-4(x-4) | | 10-3*x=x+4 | | -9=6+5v | | 3y+7=5y+1 | | 32x+(-32x+25)=12 | | 142,000,000/1.19 | | 12x-20=7x+20 | | f(20)=0.05x+3 | | 9c-4=26-c | | 50=5(3m-2) | | -15(-B)= | | 1/4=2/x | | -42=4t | | d/5-3=-4 | | 7+3t=5t-1 | | -0.6k-1+0.5k=3 | | g/10=10 |